Azacitidine for Front-Line Therapy of Patients with AML: Reproducible Efficacy Established by Direct Comparison of International Phase 3 Trial Data with Registry Data from the Austrian Azacitidine Registry of the AGMT Study Group - Pleyer, Lisa (Int J Mol Sci, 2017)
We recently published a clinically-meaningful improvement in median overall survival (OS) for patients with acute myeloid leukaemia (AML), >30% bone marrow (BM) blasts and white blood cell (WBC) count ≤15 G/L, treated with front-line azacitidine versus conventional care regimens within a phase 3 clinical trial (AZA-AML-001; NCT01074047; registered: February 2010). As results obtained in clinical trials are facing increased pressure to be confirmed by real-world data, we aimed to test whether data obtained in the AZA-AML-001 trial accurately represent observations made in routine clinical practice by analysing additional AML patients treated with azacitidine front-line within the Austrian Azacitidine Registry (AAR; NCT01595295; registered: May 2012) and directly comparing patient-level data of both cohorts. We assessed the efficacy of front-line azacitidine in a total of 407 patients with newly-diagnosed AML. Firstly, we compared data from AML patients with WBC ≤ 15 G/L and >30% BM blasts included within the AZA-AML-001 trial treated with azacitidine (“AML-001” cohort; n = 214) with AAR patients meeting the same inclusion criteria (“AAR (001-like)” cohort; n = 95). The current analysis thus represents a new sub-analysis of the AML-001 trial, which is directly compared with a new sub-analysis of the AAR. Baseline characteristics, azacitidine application, response rates and OS were comparable between all patient cohorts within the trial or registry setting. Median OS was 9.9 versus 10.8 months (p = 0.616) for “AML-001” versus “AAR (001-like)” cohorts, respectively. Secondly, we pooled data from both cohorts (n = 309) and assessed the outcome. Median OS of the pooled cohorts was 10.3 (95% confidence interval: 8.7, 12.6) months, and the one-year survival rate was 45.8%. Thirdly, we compared data from AAR patients meeting AZA-AML-001 trial inclusion criteria (n = 95) versus all AAR patients with World Health Organization (WHO)-defined AML (“AAR (WHO-AML)” cohort; n = 193). Within the registry population, median OS for AAR patients meeting trial inclusion criteria versus all WHO-AML patients was 10.8 versus 11.8 months (p = 0.599), respectively. We thus tested and confirmed the efficacy of azacitidine as a front-line agent in patients with AML, >30% BM blasts and WBC ≤ 15 G/L in a routine clinical practice setting. We further show that the efficacy of azacitidine does not appear to be limited to AML patients who meet stringent clinical trial inclusion criteria, but instead appears efficacious as front-line treatment in all patients with WHO-AML.